A tradução como lugar específico : uma mirada sobre as obras Juntamentz, de Raquel Garbelotti, e On Translation, de Antoni Muntadas - Sartório, Pólen Pereira (2016)
This thesis explores issues of translation and contemporary artistic practices thought in a site specific way, investigating if it is possible to create a parallel between the translation process and the appropriation process of a site to create an artwor